Analisis Korelasi Jenis Persalinan dengan Kejadian Sindroma Baby Blues - Rahmawati, Rahmawati; Saida, Saida (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Baby Blues Syndrome or often also called Maternity Blues is understood as a mild affective disorder syndrome that often appears in the first week after delivery and peaks on the third to fifth day and attacks within 14 days after delivery. The incidence of baby blues or postpartum blues in Asia is quite high and varies between 26-85%, while in Indonesia the incidence of baby blues or postpartum blues is between 50-70% of postpartum women. This study aims to see the correlation between the type of delivery and the incidence of baby blues syndrome in the working area of ​​the Benu-Benua Public Health Center, Kendari City. The research method used was an observational analytic study with a cross-sectional design which was carried out in June 2020 at the Benu-Benua Health Center working area involving 53 mothers who gave birth. The results showed that the preponderance of experiencing baby blues and how to give birth normally. The results of the Spearman test show that the correlation between variables is significant. The conclusion of this study is that there is a correlation between the type of delivery and the incidence of baby blues syndrome.